(untitled) (Quaestiones Disputatae: temas en debate, 2021)
This article aims to present the work carried out by some researchers who proposed research projects with the participation of different communities from the understanding of their perceptions of peace, with the intervention guided towards its constituent elements and converging towards the same objective, focused on peacebuilding. The communities involved range from children from Pirgua, a village near Tunja, university students from the University of Santo Tomás and, finally, inmates from the maximum security prison in Combita. Three types of population with different characteristics that, through the activities of the proposed projects, carried out actions to improve their environment and build peace from their territory, based on a model of social and, above all, human development.